Hepatitis E virus seroprevalence in indigenous residents of the Hà Giang northern province of Vietnam - E. V. Lichnaia; T.H. G. Pham; O. A. Petrova; T. N. Tran; T. T. Nguyen; T.T. N. Bui; V. C. Vo; A. V. Dmitriev; O. V. Kalinina (Инфекция и иммунитет, 2021)
Vietnam is an endemic territory of the South-East Asia in terms of the prevalence of hepatitis E virus. However, the data on the prevalence of HEV infection among the indigenous population of Vietnam are limited, whereas the data on various minor ethnic groups are not available. Рopulation of the Northern province Hà Giang is characterized by ethnic diversity and consists of about 22 ethnic groups that have preserved their ethnic identity determining the features of their lifestyle and farming. The goal of the current study was to conduct a cross-sectional examination to assess prevalence of serological markers of HEV infection in the indigenous population of the Northern province of Vietnam, Hà Giang. Materials and methods. A total of 1127 healthy indigenous residents aged 18 to 83 years (average age 42.8±1.5) who lived in three regions (Yên Minh, Bắc Mê and Đông Văn) of Hà Giang province in 2019 were enrolled in the study. The presence of HEV-specific IgG antibodies (anti-HEV IgG) was determined by the ELISA using kits “DS-IFA-ANTI-HEV-G” (LLC NPO “Diagnostic Systems”, Russia). Results. The prevalence of anti-HEV IgG antibodies in the indigenous population in the Hà Giang province was 74.4% (838/1127; 95% CI 71.7–76.8), with the peak occurrence of anti-HEV IgG (87.6%) found in Đông Văn region, which was significantly higher compared to those in the Bắc Mê (χ2 = 16.37, p = 0.000052) and Yên Minh (χ2 = 214.64, p < 0.00001) regions. The Yên Minh Region was characterized by the lowest percentage of subjects involved in the epidemic process (χ2 = 77.55, p < 0.00001). No significant gender-related differences were detected in antiHEV IgG level both in general and in individual regions. The peak frequency of anti-HEV IgG (85.9%) was found in the H’mong ethnic group, which was significantly higher than in the Tay ethnic groups (χ2 = 77.32, p < 0.00001) and in the remaining minor ethnic groups (χ2 = 63.44, p < 0.00001). Conclusion. The results of this study indicate a high seroprevalence of hepatitis E virus in the minor ethnic groups, which preserve the national lifestyle in the Hà Giang province of the Northern Vietnam. As the Hà Giang province is located in remote mountain areas, a number of which are still difficult to access, its low economic status, poor sanitary and hygienic living conditions, lack of high-quality water supply, multinational population following different lifestyles, the contact of population with natural potential sources of HEV infection, including various wild and domestic animals, contribute to the successful spread of the hepatitis E virus in the region and the involvement of all populational age groups in the epidemic process. Taking into account the rapid development of the tourism industry in the Hà Giang Province particularly in the Đông Văn Region, where the Đông Văn Karst Plateau Geopark being recognized by UNESCO as national treasure is located, the results of this study emphasize a need to plan and perform the events aimed for preventing and monitoring HEV infection in endemic regions in Vietnam in order to reduce a risk of spread of hepatitis E virus not only inside, but also outside the country.